Androgen-deprivation therapy-induced aggressive prostate cancer with neuroendocrine differentiation - Julia Lipianskaya; Alexa Cohen; Clark J Chen; Elaine Hsia; Jill Squires; Zhen Li; Yaqun Zhang; Wei Li; Xufeng Chen; Hua Xu; Jiaoti Huang (Asian Journal of Andrology, 2014)
Most prostate cancers (PCas) are classified as acinar type (conventional) adenocarcinoma which are composed of tumor cells with luminal differentiation including the expression of androgen receptor (AR) and prostate-specific antigen (PSA). There are also scattered neuroendocrine (NE) cells in every case of adenocarcinoma. The NE cells are quiesecent, do not express AR or PSA, and their function remains unclear. We have demonstrated that IL8-CXCR2-P53 pathway provides a growth-inhibitory signal and keeps the NE cells in benign prostate and adenocarcinoma quiescent. Interestingly, some patients with a history of adenocarcinoma recur with small cell neuroendocrine carcinoma (SCNC) after hormonal therapy, and such tumors are composed of pure NE cells that are highly proliferative and aggressive, due to P53 mutation and inactivation of the IL8-CXCR2-P53 pathway. The incidence of SCNC will likely increase due to the widespread use of novel drugs that further inhibit AR function or intratumoral androgen synthesis. A phase II trial has demonstrated that platinum-based chemotherapy may be useful for such therapy-induced tumors.